Using Go-Alongs for exploring immigrant entrepreneurs' native customers. (November 2017) - Parzer, Michael; Rieder, Irene; Wimmer, Eva
The purpose of this article is to evaluate the methodological practice of Go-Alongs for exploring immigrant entrepreneurs' native customers, a barely developed subfield within immigrant business research. Through accompanying individuals on outings in their familiar environments, Go-Alongs as a qualitative data collection method are used to gain access to practices, experiences and interpretations of individuals in their everyday routines. Drawing on current qualitative research on native customers in immigrant grocery shops in Vienna, the article demonstrates how Go-Alongs can be used for exploring consumption practices and patterns of interethnic interaction in this specific setting. What becomes apparent is that Go-Alongs provide an opportunity to gain access to reflexive aspects of lived experience in situ, in the present case expressed by spontaneous and emotional comments when the shop, ethnic products or interethnic interactions are commented on and evaluated. Moreover, Go-Alongs allow insights into modes of self-expression. However, Go-Alongs have limitations as they cannot capture consumption practices beyond the limited time and space of shopping. Furthermore, they do not fully provide access to narratives and discourses; therefore, Go-Alongs are most useful in combination with in-depth interviews.